Phytosociological analysis of the Sidi Boughaba Biological Reserve, Kénitra, Morocco - Challi, Dounia; Dahmani, Jamila; Jdi, El Habib; Belahbib, Nadia (Hacquetia, 2023)
The biological reserve of Sidi Boughaba has a unique plant biodiversity, with many animals, including birds, finding refuge there. Data on this biodiversity is old and incomplete. This phytosociological study was carried out to define the vegetation structure of the area. Stratified sampling was carried out and 124 relevés were recorded. Multivariate statistical analyses (correspondence factorial analysis and hierarchical ascending classification) used to process the relevés revealed the presence of 9 plant groups, including 4 plant associations and 5 subassociations, which belong to 3 phytosociological classes (Ammophiletea, Quercetea ilicis and Querco roboris-Fagetea sylvaticae). Quercetea ilicis is the most widespread in the area, showing several successional stages on grey and consolidated dunes. Vegetation of Ammophiletea can only be found on mobile sand. Vegetation of the class Querco roboris-Fagetea sylvaticae occupies an inter-dunar depression on hydromorphic soil. The association Pterido aquilinum-Populetum albae is newly described as five sub-associations of Clematido cirrhosae-Juniperetum lyciae.